2004
DOI: 10.1089/153056204773644571
|View full text |Cite
|
Sign up to set email alerts
|

Telehomecare: A Comparison of Three Canadian Models

Abstract: The delivery of health care is often segmented into sectors. In Canada, hospital care has traditionally been distinct from community care, and thus the transition of patients across sectors has been challenging. This paper focuses on the systematic development of an integrated model of care for children, for the purpose of smoothing the transition from hospital to home. The new service model uses emerging telecommunications technology to link hospital care providers to patients at home and is termed "telehomec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Worldwide, many initiatives target some of these factors: the three assessment tools developed in the UK documenting care progress and planning end of life care61 – 64; home based models of palliative care such as in North America where more than 90% of these services are provided at home; tele-homecare, used in the US, Canada, Japan, and Europe6568; the inclusion of training in end of life care as mandatory for physicians; and the compassionate care benefits, in the form of a paid leave for carers of dying patients implemented by the Canadian government since January 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, many initiatives target some of these factors: the three assessment tools developed in the UK documenting care progress and planning end of life care61 – 64; home based models of palliative care such as in North America where more than 90% of these services are provided at home; tele-homecare, used in the US, Canada, Japan, and Europe6568; the inclusion of training in end of life care as mandatory for physicians; and the compassionate care benefits, in the form of a paid leave for carers of dying patients implemented by the Canadian government since January 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Parental caregivers were mostly of paediatric cases including new parents after childbirth (5%), 23,24,54 parents of premature or low birth-weight infants (3%), 55,56 of children with chronic disease 18,57,58 or disability (asthma, 13,5962 renal disease, 63 heart disease, 64 diabetes, 65,66 obesity, 14 brain injury, 10 hearing loss 22 and autism 12,67 ) (26%), of children with mental or behavioural disease (psychiatric disorders, 15,19,68 attention-deficit hyperactivity disorder (ADHD), 69,70 and oppositional or disruptive behaviour 21,71,72 ) (12%), of children in end-of-life care (2%), 73 and of preschool children (2%). 74 …”
Section: Resultsmentioning
confidence: 99%
“…The telehealth technologies used in the studies included: video (videoconferencing or videophone) (40%) (Table 1, see online archive), 10,1316,1820,2225,30,35,42,43,4850,54,55,57,58,62,64,69 telephone-based (phone call or text message) (31%) (Table 2, see online archive), 11,17,21,26,27,3234,37,39,44–47,60,65,66,68,72,74 web-based information (18%) (Table 3, see online archive), 12,36,38,51,56,59,61,63,67,70,71,73 and telemetry/remote monitoring (electronic data collection) (11%) (Table 4, see online archive). 28,29,31,40,41,52,53 Video was the most commonly-used technology.…”
Section: Resultsmentioning
confidence: 99%
“…1 Telehomecare has been defined as a new service model using emerging telecommunications technology to link healthcare providers to patients at home. 2 Telehomecare constitutes a means to facilitate access for several groups of patients who often lack home care services. 3,4 Numerous pilot studies have demonstrated a trend that telehomecare technology may improve patient outcomes through timely intervention and crises prevention, thereby reducing return visits to physician offices and hospitals.…”
Section: Introductionmentioning
confidence: 99%